STUDI LITERATUR: EFEKTIVITAS MODEL FLIPPED CLASSROOM TERHADAP MANAJEMEN WAKTU PEMBELAJARAN MATEMATIKA - Rosiani Feti Thanelab Nope; Nurfadilah; Asdar (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to comprehensively examine the effectiveness of the Flipped Classroom model on mathematics learning time management through a literature review approach. The research method used is a literature review by analyzing and synthesizing findings from ten relevant studies published between 2020 and 2025, obtained from the Google Scholar and Semantic Scholar databases. The results of the study show that the consistent application of the Flipped Classroom is able to optimize the use of face-to-face time by shifting the delivery of material to independent learning before class, so that class time can be focused on discussion, problem solving, and deepening concepts. In addition to increasing time efficiency, this model also contributes positively to student active engagement, concept understanding, learning achievement, and interest in mathematics. However, several challenges in its implementation were also identified, including the high time requirement for material preparation, limited guidance during independent learning, and dependence on technological readiness. Overall, the Flipped Classroom is an effective learning alternative to support mathematics learning time management when designed and implemented appropriately.